Living Well in a World Worth Living in for All: Volume 1: Current Practices of Social Justice, Sustainability and Wellbeing - Reimer, Kristin Elaine; Kaukko, Mervi; Windsor, Sally; Mahon, Kathleen; Kemmis, Stephen (Springer Nature, 2023)
This open access book is the first of a two-volume series focusing on how people are being enabled or constrained to live well in today’s world, and how to bring into reality a world worth living in for all. The chapters offer unique narratives drawing on the perspectives of diverse groups such as: asylum-seeking and refugee youth in Australia, Finland, Norway and Scotland; young climate activists in Finland; Australian Aboriginal students, parents and community members; families of children who tube feed in Australia; and international research students in Sweden. The chapters reveal not just that different groups have different ideas about a world worth living in, but also show that, through their collaborative research initiative, the authors and their research participants were bringing worlds like these into being. The volume extends an invitation to readers and researchers in education and the social sciences to consider ways to foster education that realises transformed selves and transformed worlds: the good for each person, the good for humankind, and the good for the community of life on the planet. The book also includes theoretical chapters providing the background and rationale behind the notion of education as initiating people into ‘living well in a world worth living in'. An introductory chapter discusses the origins of the concept and the phrase.